Total contact casts versus removable offloading interventions for the treatment of diabetic foot ulcers: a systematic review and meta-analysis - Li, Bin; Lin, Aifang; Huang, Jianping; Xie, Jianying; Liu, Quanyong; Yang, Chenxi; Zhang, Zhengmao (Frontiers in Endocrinology, 2023)
Objective: This study aimed to evaluate the effectiveness of total contact casts (TCCs) versus removable offloading interventions among patients with diabetic foot ulcers (DFUs).: A comprehensive search was done in databases Embase, Cochrane Library, and, PubMed. The references of retrieved articles were reviewed, up until February 2023. Controlled trials comparing the effects of TCCs with removable offloading interventions (removable walking casts and footwear) in patients with DFUs were eligible for review.Results: Twelve studies were included in the meta-analysis, involving 591 patients with DFUs. Among them, 269 patients were in the intervention group (TCC), and 322 in the control group (removable walking casts/footwear). The analysis revealed that the TCC group had higher healing rates (Risk Ratio(RR)=1.22; 95% confidence interval(CI):1.11 to 1.34, p<0.001), shorter healing time (Standard Mean Difference(SMD)=-0.57; 95%CI: -1.01 to -0.13, P=0.010), and elevated occurrence of devicerelated complications (RR=1.70; 95%CI:1.01 to 2.88, P=0.047), compared with the control group. Subgroup analysis illustrated patients using TCCs had higher healing rates than those using removable walking casts (RR=1.20; 95%CI:1.08 to 1.34, p=0.001) and footwear (RR=1.25; 95%CI:1.04 to 1.51, p=0.019), but they required comparable time for ulcer healing compared with those using removable walking casts (SMD=-0.60; 95%CI: -1.22 to 0.02, P=0.058) or footwear group (SMD=-0.52; 95%CI:-1.17 to 0.12, P=0.110). Although patients using TCCs had significantly higher incidence of devicerelated complications than those using footwear (RR=4.81; 95%CI:1.30 to 17.74, p=0.018), they had similar one compared with those using the removable walking casts (RR=1.27; 95%CI:0.70 to 2.29, p=0.438).The use of TCCs in patients with DFUs resulted in improved rates of ulcer healing and shorter healing time compared to removable walking casts and footwear. However, it is important to note that TCCs were found to be associated with increased prevalence of complications.